1987
DOI: 10.1111/j.1432-1033.1987.tb13635.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of the gene encoding cholinephosphate cytidylyltransferase in Saccharomyces cerevisiae

Abstract: 1. The structural gene for cholinephosphate cytidylyltransferase (CCT) was isolated from a Sacchuromyces cerevisiae genomic library by means of complementation in a mutant of the yeast defective in the enzyme. The cloned DNA restored both the growth and cholinephosphate cytidylyltransferase activity of the mutant. Whereas the enzyme of the mutant was thermolabile, the enzyme produced by the transformant was indistinguishable in heat stability from that produced by the wild type.2. Strains carrying a multicopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 47 publications
3
69
0
Order By: Relevance
“…falciparum CCT gene. Only two CCT genes, from yeast [37] and rat liver [38], had been cloned when this study was initiated. Our strategy for cloning the P ,fulcipurum CCT gene was to obtain a specific DNA probe rather than relying on heterologous hybridization, which was unlikely, due to the biased codon usage of l?…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…falciparum CCT gene. Only two CCT genes, from yeast [37] and rat liver [38], had been cloned when this study was initiated. Our strategy for cloning the P ,fulcipurum CCT gene was to obtain a specific DNA probe rather than relying on heterologous hybridization, which was unlikely, due to the biased codon usage of l?…”
Section: Resultsmentioning
confidence: 99%
“…Tsukagoshi and his colleagues [37] have already shown that significant degrees of local similarity exist among the yeast CCT, E. coli CDP-diacylglycerol pyrophosphatase, E. coli DNA polymerase, E. coli 3-deoxy-manno-octulosonate cytidylyltransferase and T4 DNA ligase. It should be noted that all these enzymes are involved in a nucleotidyl transfer reaction.…”
Section: Properties Of the Predictedmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in several genes (CKI1, PCT1, CPT1, KES1, BSD1, BSD2) also suppress the secretory defects of sec14 mutants (12,14). Three genes (CKI1, PCT1, CPT1) encode enzymes in a PtdCho biosynthesis pathway (61)(62)(63) and KES1 encodes an oxysterol-binding protein (64). Furthermore, Pld1p (a phospholipase D), which is activated in sec14 mutants (65), is required for these mutations to suppress sec14 defects (65,66), suggesting that the sec14 suppression by these mutations takes place only when basal PtdCho levels are decreased or phosphatidic acid levels are elevated.…”
Section: Delivery Of Cpy To the Vacuole Is Not Blocked In Pik1 Tsmentioning
confidence: 99%
“…In the CDP-DAG pathway, PC is synthesized from CDP-DAG via the reactions catalyzed by PS synthase (18 -20), PS decarboxylase (21)(22)(23), PE methyltransferase (24,25), and phospholipid methyltransferase (24,26). In the CDP-choline branch of the Kennedy pathway, PC is synthesized from choline via the reactions catalyzed by choline kinase (27), phosphocholine cytidylyltransferase (28), and choline phosphotransferase (29,30). Analyses of mutations in S. cerevisiae (4,31,32), as well as in mammalian cells (33,34) indicate that the physiological role(s) of PC synthesized by the two pathways are different.…”
mentioning
confidence: 99%